Hot summer nights [videorecording (DVD)] - Bynum, Elijah; Chalamet, Timothée; Roe, Alex, 1990-; Monroe, Maika; Mitchell, Maia (Lionsgate, 2018)
"Recent high school graduate Daniel Middleton comes to Cape Cod to spend his last summer before college with his aunt. The awkward teenager struggles to fit in until he meets local drug dealer Hunter Strawberry. Daniel quickly gets in over his head dealing drugs and falling for Hunter's mysterious and beautiful younger sister McKayla. The web of lies, angst, betrayal and desire comes to a head amidst the approach of a hurricane in the summer of 1991." --